Postmortem Commercial Rights: The Legal Status of Deceased Persons in Business Transactions - NNEBUIHE, Linda Iheanacho (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
The legal status of deceased persons in business transactions remains a complex and underexplored frontier in commercial law. This paper investigates postmortem commercial rights—the enduring contractual, intellectual property, and digital asset rights that persist after death—and highlights jurisdictional inconsistencies in their treatment. While traditional frameworks like succession law and probate procedures govern tangible assets, emerging realities such as e-commerce stores, AI-generated endorsements, and posthumous brand deals expose critical gaps in legal systems globally. Through doctrinal analysis and comparative case studies (e.g., Prince Estate v. Legacy Recordings and Nigeria’s Lawan v. Yunusa), this study reveals tensions between commercial certainty and heirs’ rights, particularly where digital assets or unfinished contracts lack clear succession mechanisms. The paper argues that current laws inadequately address postmortem liabilities (e.g., debts, executory contracts) and novel commercial actors (e.g., deepfake personas), risking economic disruption and ethical violations. A focused evaluation of Nigeria’s legal landscape under the Companies and Allied Matters Act (CAMA) and data protection regulations exemplifies these challenges in hybrid jurisdictions. The study concludes with policy recommendations, including standardized postmortem contractual clauses, legislative clarity for digital asset inheritance, and ethical guardrails for posthumous AI applications. By bridging commercial law, succession law, and emerging technologies, this research contributes to debates on legal personhood and proposes reforms to align postmortem rights with 21st-century business realities.